Adaptation in likelihood trials - Blume, Jeffrey (Henry Stewart Talks, 2017)
The law of likelihood, Binomial likelihood, Some advantages, Frequency properties, Error rates, Likelihood’s evidential metrics, Likelihood strategy for adaption, Stimulation set-up, Analysis model